Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 8)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 8)" [g0973008.jpg], n.d.